Half pins stress shielding interaction behavior at implant-bone interface - Ibrahim, Nur Fatin Izzati; Daud, Ruslizam; Ali Hassan, Muhammad Khairul; Md Zain, Noor Alia; Bajuri, Yazid (International Journal of Integrated Engineering, 2018)
External fixator (EF) is assembled by pin, ring, rods and locking devices. Pin implantation is used to provide stability for bone healing and osseointegration. Clinical failure of screw implant is reported to occur at the end of screw thread due to screw loosening and screw tightening. It is hypothesized that the same failure mechanism is occurred for pins. This paper presents the finite element (FE) analysis of EF implantation of different half pins on diaphysis of femur bone. Tapered conical half-pin and trocar-tip tapered half- pin were analysed using four types of materials (titanium alloy, stainless steel, magnesium alloy and carbon fiber) to determine the von-Mises stress and stress shielding. It is found that the pins were yielded at the thread of pin near to hard-soft tissue interface, which is agreed with the clinical screw implant fracture. However, magnesium alloy has the lower von- Mises and greater stress shielding (STP) transfer. Thus, trocar-tip tapered magnesium alloy half pin is predicted to be the best material for better stability of bone fixation.